The CXCR4-LASP1-eIF4F Axis Promotes Translation of Oncogenic Proteins in Triple-Negative Breast Cancer Cells - Howard, Cory M.; Bearss, Nicole; Subramaniyan, Boopathi; Tilley, Augustus; Sridharan, Sangita; Villa, Nancy; Fraser, Christopher S.; Raman, Dayanidhi (Frontiers in Oncology, 2019)
Triple negative breast cancer (TNBC) remains clinically challenging as effective targeted therapies are lacking. In addition, patient mortality mainly results from the metastasized lesions. CXCR4 has been identified to be one of the major chemokine receptors involved in breast cancer metastasis. Previously, our lab had identified LIM and SH3 Protein 1 (LASP1) to be a key mediator in CXCR4-driven invasion. To further investigate the role of LASP1 in this process, a proteomic screen was employed previously and identified a novel protein-protein interaction between LASP1 and components of eukaryotic initiation 4F complex (eIF4F). We hypothesized that activation of the CXCR4-LASP1-eIF4F axis may contribute to the preferential translation of oncogenic mRNAs leading to breast cancer progression and metastasis. To test this hypothesis, we first confirmed that the gene expression of CXCR4, LASP1, and eIF4A are upregulated in invasive breast cancer. Moreover, we demonstrate that LASP1 associated with eIF4A in a CXCL12-dependent manner via a proximity ligation assay. We then confirmed this finding and the association of LASP1 with eIF4B via co-immunoprecipitation assays. Furthermore, we show that LASP1 can interact with eIF4A and eIF4B through a GST-pulldown approach. Activation of CXCR4 signaling increased the translation of oncoproteins downstream of eIF4A. Interestingly, genetic silencing of LASP1 interrupted the ability of eIF4A to translate oncogenic mRNAs into oncoproteins. This impaired ability of eIF4A was confirmed by a previously established 5’-UTR luciferase reporter assay. Finally, lack of LASP1 sensitizes 231S cells to pharmacological inhibition of eIF4A by Rocaglamide A as evident through BIRC5 expression. Overall, our work identified the CXCR4-LASP1 axis to be a novel mediator in oncogenic protein translation. Thus, our axis of study represents a potential target for future TNBC therapies.